Institutional Barriers for Sustainable Transport - Curtis, Carey; Low, N. (Ashgate, 2012)
In a world seeking to tackle global environmental problems such as climate change, the importance of local and national institutional change to deal most effectively with these issues is critical. This book presents an investigation of the institutional barriers preventing the development of a new vision for urban transport compatible with these realities and in those terms 'sustainable'. Through an examination of transport planning in Australia, the book challenges conventional wisdom by showing, through original research, how 'car dependence' is as much an institutional as a technical phenomenon. The authors' case studies in three metropolitan cities show how transport policy has become institutionally fixated on a path dominated by private, road-based transport and how policy systems become encrusted around investment to accommodate private cars, erecting an impenetrable barrier against more sustainable mobility and accessibility solutions. Representing a new approach to understanding transport policy, this book brings sophisticated political-institutional analysis to what has traditionally been the domain of engineering and technology. The authors connect the empirical content to this theory and the issue of sustainability making the findings applicable to most cities of the developed world, and to fields beyond transport planning. A strategy and program of action is outlined to take advantage of changing public perceptions and aimed at creating a new vision for urban transport.